Development of Meme Learning Media with PMRI to Implement Mathematics Literacy in Students Elementary School - Wathani, Diki Hasrul; Irawati, Riana; Iswara, Prana Dwija (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Low mathematical literacy is one of the causes of the lack of interest and motivation in learners. Mathematical literacy and realistic mathematical approaches have relevant characteristics. This research aims to develop memes as learning media with a realistic mathematical approach to develop mathematical literacy in elementary school students. The research consists of several steps, which are: analysis, design, development, implementation, and evaluation. The methods used are descriptive, evaluative, and experimental with a pre- experimental design. The instruments used were expert validation questionnaires, student response questionnaires, teacher observation sheets, and evaluation assessments. The results obtained from material experts were 79% and 78% from media expert, both in the appropriate category. Assessments of mathematical content obtained the validation results from the material experts and media experts with scores of 79% and 78%; both belong to the decent category. In large-scale trials, the results of the student response questionnaire after learning obtained a score of 73% while the evaluation results obtained a score of 60%. The students' evaluation scores are evenly distributed from the lower limit of 25 to the upper limit of 95. Based on the results, it can be concluded that meme teaching media with a realistic mathematical approach develop students’ mathematical literacy even though it is not a high level.DOI: https://doi.org/10.22342/jpm.16.3.15249.339-350